2019
DOI: 10.5812/jjm.94687
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Antibodies Against Blood Group, HBV, and Salmonella Regarding Protein Content, Activity, and Affinity in Black and Yellow Healthy Individuals

Abstract: Background: Black and Yellow individuals of various ethnic populations may differ in the immunity to infectious diseases. Objectives: Our study aimed to explore and compare the detailed production characteristics (protein, activity, and affinity) of antibodies against blood group (natural antibodies), hepatitis B virus (HBV), and Salmonella typhi to find the differences in anti-infectious immunity between Black and Yellow populations. Methods: Serum samples of Black and Yellow healthy individuals were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the present study, our primary detection results values of antibody parameters showed a high difference in Sudanese ( Figure 1B) and among Chinese ( Figure 2B). The high antibody parameters usually develop at the end course period of infection leading to the clearance of antigens (16,34,35). In addition, our findings showed a high variation of the HLA-DQB1 alleles among Sudanese ( Figure 1A) and in Chinese (Figure 2A).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In the present study, our primary detection results values of antibody parameters showed a high difference in Sudanese ( Figure 1B) and among Chinese ( Figure 2B). The high antibody parameters usually develop at the end course period of infection leading to the clearance of antigens (16,34,35). In addition, our findings showed a high variation of the HLA-DQB1 alleles among Sudanese ( Figure 1A) and in Chinese (Figure 2A).…”
Section: Discussionmentioning
confidence: 52%
“…The affinity of S. typhi O antibody was calculated according to that described by Tamomh and Liu (34) in which serum samples were serially diluted 20-, 40-, 80-, and 160fold; then the reaction was measured under standard condition (PBS condition) and after changing the standard condition (urea condition). Finally, the values of these dilutions were analyzed using agglutination reaction method, and the corresponding agglutination reaction score values for each dilution were recorded and the value of each reaction condition calculated.…”
Section: Determination Of Antibody Affinity To Salmonella Typhi O Antmentioning
confidence: 99%
“…3 and Table 4. Complement is an element which sensitive to heat, and the level of total activity and the heat tolerance of complement varies between individuals may express the state of various infections or diseases, and differences of individuals immune responses [1,6,7,29,30]. Accordingly, measuring and detecting the total activity and heat tolerance of complement between two ethnic groups, as Sudanese and Chinese populations, could expect or predict the health status or individuals immune status.…”
Section: Discussionmentioning
confidence: 99%